Death by prison : the emergence of life without parole and perpetual confinement - Seeds, Christopher, 1967- (University of California Press, 2022)
"In recent decades, life imprisonment without the possibility of parole (LWOP) has developed into a distinctive penal form in the United States, one firmly entrenched in US policy-making, judicial and prosecutorial decision-making, correctional practice, and public discourse. LWOP is now a routine part of contemporary US criminal justice, even engrained in the nation's cultural imaginary, but how it came to be so remains in question. Fifty years ago, imprisoning a person until death was an extraordinary sentence; today, it accounts for an increasing percentage of all US prisoners. What explains the shifts in penal practice and the social imagination by which we have become accustomed to imprisoning individuals until death without any reevaluation or reasonable expectation of release? Combining a wide historical lens with detailed state- and institutional-level research, Death by Prison offers a provocative new foundation for questioning this deeply problematic practice that has escaped close scrutiny for too long. The rise of life without parole, this book demonstrates, is not simply a matter of growth: it is a phenomenon of change, inclusive of changes in definitions, practices, and meanings. Death by Prison shows that the complex processes by which life without parole became imprisonment until death and perpetual confinement became a routine part of American punishment must be understood not only in terms of punitive attitudes and political efforts but as a matter of background conditions and transformations in penal institutions. The book also reveals how the social and sociological relevance of life without parole extends beyond its punitive element: imbued in the history of life without parole are a variety of forms of disregard--for human dignity, for social consequences, and for the myriad responsibilities that go along with state punishment"--